2011
DOI: 10.1017/s175577391000041x
|View full text |Cite
|
Sign up to set email alerts
|

Crafting tolerance: the role of political institutions in a comparative perspective

Abstract: Ongoing changes in social structures, orientation, and value systems confront us with the growing necessity to address and understand transforming patterns of tolerance as well as specific aspects, such as social tolerance. Based on hierarchical analyses of the latest World Values Survey (2005-08) and national statistics for 28 countries, we assess both individual and contextual aspects that influence an individual's perception of different social groupings. Using a social tolerance index that captures persona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(58 citation statements)
references
References 65 publications
(197 reference statements)
0
55
2
Order By: Relevance
“…Eger (2010) as well as Mau and Burkhart (2009) already showed that rising levels of ethnic heterogeneity decrease welfare state solidarity. We thus argue that the assumed positive effect of welfare states on the formation of tolerance (Crepaz and Damron, 2009;Kirchner et al, 2011) may not hold for highly ethnic diverse countries. Following the approach by van Oorschot and Uunk (2007) who scrutinized the relationship between welfare state spending and the public's concern for immigrants, we extend their study by combing insights from the welfare state solidarity literature with evidence from tolerance research.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Eger (2010) as well as Mau and Burkhart (2009) already showed that rising levels of ethnic heterogeneity decrease welfare state solidarity. We thus argue that the assumed positive effect of welfare states on the formation of tolerance (Crepaz and Damron, 2009;Kirchner et al, 2011) may not hold for highly ethnic diverse countries. Following the approach by van Oorschot and Uunk (2007) who scrutinized the relationship between welfare state spending and the public's concern for immigrants, we extend their study by combing insights from the welfare state solidarity literature with evidence from tolerance research.…”
Section: Introductionmentioning
confidence: 84%
“…Previous studies have shown that institutional settings such as the welfare regime (e.g. Crepaz and Damron, 2009;Kirchner et al, 2011), the political system (e.g. Dunn et al, 2009;Peffley and Rohrschneider;Weldon, 2006) as well as economic factors (e.g.…”
Section: How Does the Welfare State Relate To Tolerance?mentioning
confidence: 99%
See 1 more Smart Citation
“…Third, it is necessary to broaden the scope of the dependent variable considering other measures of tolerance. Although the measure used here is similar to other international studies (Kirchner et al, 2011), a study like this should ideally use a two-step measurement procedure to first establish that an individual has an objection toward a particular group, and second to measure the extent to which the individual supports or opposes that group.…”
Section: Resultsmentioning
confidence: 99%
“…Another way of measuring tolerance that has been used in the study reported here is to examine participants' explicit attitudes or the degree of their positive attitudes (Weldon, 2006;Kirchner, Freitag, & Rapp, 2011;Miklikowska, 2016). That approach is often used in psychological and sociological literature, in which tolerance relates to the appreciation and affirmation of diversity, pluralism, and difference-that is, the more positive aspect of the concept of tolerance.…”
Section: Tolerance: the Dependent Variablementioning
confidence: 99%